Boriding of Low-Carbon Steel by Plasma Method: Microstructure and Coating Properties - Nguyen Van Vinh; Nguyen Trung Thuy; Balanovskiy Andrey Evgenievich (Tribology in Industry, 2024)
In materials science, steel boration is a promising type of thermochemical diffusion process, the purpose of which is the introduction of hard and wear-resistant boride particles into the surface layers of the metal. The main disadvantage of boration is the fragility of borated layers, especially boride. Currently, there are promising methods for the formation of a composite structure, which are based on the treatment of surface layers of steels with concentrated energy flows (laser, electron beam and plasma). The work includes studies of microstructure, hardness measurements, analysis of phase composition, and determination of chemical composition in local locations, wear tests under various conditions, and adhesion testing of the coatings obtained after plasma boration. As the degree of alloying of the molten layer decreases in the direction from the surface to the base metal, zones of overeutectic, eutectic and pre-eutectic types with a different combination of structural components are formed. The material obtained after borating a mixture of 40% B + 10% Fe is characterized by the highest level of microhardness, which is 1000...1300 HV. The highest results in friction tests are provided by boration of a powder mixture of 40% B + 10% Fe.